Inflammatory Bowel Disease and Risk of Colorectal Cancer: An Overview From Pathophysiology to Pharmacological Prevention - Lucafò, Marianna; Curci, Debora; Franzin, Martina; Decorti, Giuliana; Stocco, Gabriele (Frontiers in Pharmacology, 2021)
Increased risk of colorectal cancer (CRC) in inflammatory bowel disease (IBD) patients has been attributed to long-standing chronic inflammation, with the contribution of genetic alterations and environmental factors such as the microbiome. Moreover, accumulating data indicate that IBD-associated CRC (IBD-CRC) may initiate and develop through a pathway of tumorigenesis distinct from that of sporadic CRC. This mini-review summarizes the current knowledge of IBD-CRC, focusing on the main mechanisms underlying its pathogenesis, and on the important role of immunomodulators and biologics used to treat IBD patients in interfering with the inflammatory process involved in carcinogenesis.